Pandangan Tokoh Adat dan Pergeseran Nilai-nilai Etika Pergaulan Remaja: Studi di Kota Menggala Kabupaten Tulang Bawang - Khalik, Abu Tholib (Fakultas Filsafat, Universitas Gadjah Mada Yogyakarta, 2000)
Menggala city that is estimated had born since 1541 with its homogen people and its strong tradition in society living. Even though this city had been ever become international port, but the power of society culture is still steady. After new order era, poorly, there is movement of norm phenomenon that seen clearly, especially in youth relationship ethics.Since colonial until new order era, the leaders of its tradition still capable to become model and builder for the society in culture and religion field. But, now they almost powerless and very urgent to be strife for look after culture field as national asset. For this purpose, it is needed same vision, mission and concrete action from the founders, tradition, and society leaders, or officer including its local bureaucrats, in order to work together to build up their culture and religion norm at all society level